Family composition and living arrangements-Cross‐sectional study on family involvement to self‐managed rehabilitation of people with coronary artery disease - Sonja Tuomisto; Meeri Koivula; Päivi Åstedt‐Kurki; Mika Helminen (Wiley, 2020)
Abstract Aim To describe the family composition and living arrangements of persons diagnosed with coronary artery disease and those relationships to family involvement in self‐managed rehabilitation. Design A cross‐sectional study. Methods Data were collected with postal questionnaire from persons diagnosed with coronary artery disease (CAD) by using the Family Involvement in Rehabilitation (FIRE) scale. It measures family members' promotion of patients' rehabilitation and issues encumbering rehabilitation in family. Statistical methods were used to analyse the data. Results Patients' gender and having children in the family were predictors of issues encumbering rehabilitation in the family. But when examining living arrangements, patients who lived with a spouse or underage children had a better environment for recovery than those who lived alone or with adult children. More attention should be paid to targeting appropriate support for persons with coronary artery disease and their family members during the rehabilitation phase.